SOSIALISASI PENINGKATAN POPULASI POHON BUAH – BUAHAN DI DESA SIDORUKUN - Siti Hartati Yusida Saragih, Nadia Putri Ad’ha, Sahat Parulian Sitorus, Rahmadani Pane, Rahmi Nazlia (JURNAL BIMA, 2024)
Fruit trees are used as an alternative for greening in Sidorukun Village. Fruit trees have many benefits. Currently, many people lack food, one of which is a source of vitamins from fruit trees. This study aims to socialize the diversity of fruit trees and to determine the population and dominant types of fruit trees in Sidorukun Village. This activity will be carried out in April 2024 in Sidorukun Village, Pangkatan District, Labuhanbatu Regency. The results of the activity show that the fruit trees in Sidorukun Village consist of Banana, Rambutan, Matoa, Kedondong, Mango, Dragon Fruit, Water Guava, Longan, Lime, Kaffir Lime, Papaya, Durian, Jamaican Guava, Mangosteen, Pineapple, Stone Guava , Sapodilla and Starfruit. The fruit tree populations that dominate Sidorukun Village are the Rambutan, Mango and Banana populations.